THE EFFECT OF MITOMYCIN C ON POSTOPERATIVE PERITONEAL ADHESIONS IN MALE RATS - Soltany, Setareh (International Journal of Psychosocial Rehabilitation, 2020)
Postoperative peritoneal adhesions contribute to high morbidity and mortality rates. Fibroblast proliferation is one of the risk factors. Mitomycin C (MMC) is known to inhibit fibroblast proliferation. We herein evaluate the effect of MMC on the peritoneal adhesion in the animal model of peritoneal irrigation.Sixty-four male Wistar rats underwent a midline incision laparotomy and then were randomly assigned to eight groups. The peritoneal cavity was rinsed with injectable normal saline (NS), MMC at doses of 0.5 or 1 mg/kg with or without NS, followed by an immediate suction. The peritoneal cavity in three groups was rinsed with NS or MMC at doses of 0.5 or 1 mg/kg for 3min before suction. After 6 weeks, a laparotomy was again performed on each rat andthe adhesions were scored macroscopically withCanbaz scoring system.Animals treated with immediate MMC 1 or 3 mg/kg had the lowest incidence of postoperative adhesion. The adhesions in groups receivedeach dose of MMC, with or without saline,were significantly reduced compared with the saline group. The adhesion score was significantly lower in MMC groups (0.5 and 1mg/kg) vs. each dose of MMCs +saline or each dose of MMCs for 3min. Notably, the adhesion score was not reduced with MMC 1mg/kg (3min) compared with NS (3min), while adhesions were significantly decreased with MMC 0.5mg/kg (3min). There was no difference between NS and NS (3min).Immediate peritoneal rinsing with MMCduring the laparotomy seems to be effective in preventing the formation of postoperative adhesions.